Review on Challenges of Nutrition Intervention Research at Workplace - Pasaribu, Adi Sutriwanto; Basrowi, Ray Wagiu (Ridwan Institute, 2024)
Workplace nutrition interventions have become a popular approach to improving employee health and well-being. Nonetheless, such interventions require special attention to ethical aspects to ensure participant well-being, research integrity, and long-term benefits. A literature review was carried out using leading research databases, such as PubMed, Scopus, and Google Scholar. Keywords used include